Financial Training for MSMEs: Enhancing Financial Statement Preparation and Audit Understanding in Kembangan District - Yessie, Afly; Minanari, Minanari (CV. Proaksara Global Transeduka, 2025)
This financial training aims to enhance the understanding and skills of MSME managers in Kembangan District in financial statement preparation and financial statement audit. The training is conducted through counseling and hands-on practice methods, covering the basics of accounting, how to prepare financial statements in accordance with the financial accounting standards applicable in Indonesia, and the importance of auditing to ensure the reliability of financial statements. The training results showed a significant improvement in participants' understanding of financial statement preparation and audit processes relevant to MSME needs. This training is expected to make a tangible contribution to improving financial governance in MSMEs in Kembangan District. The program's goal is to boost business transparency, increase access to funding, improve adherence to regulations, and promote lasting business growth and development within the local MSME sector by improving financial management skills.